Diversidade fenotípica por meio de caracteres agronômicos em acessos de soja - Marconato, Marcela Bonafin [UNESP] (2014)
Soybean stands out as the most important oilseed in the world, given its nutritional and economic importance. Due to increased acreage and hence productivity, today, Brazil is the largest exporter of soybeans. However, it is observed that the genetic basis of soybean is restricted due to the unavailability of alleles able to cope with biotic and abiotic stresses fully efficiently. Thus, breeding programs aimed at increasing the genetic variability for the development of more productive and adapted cultivars. Studies regarding new sources of germplasm, such as Plant Introductions - PIs, become necessary for the identification of agronomic traits of interest to breeders. Therefore, the present work has as main objective the evaluation of agronomic performance and the genetic diversity of 93 accesses of soybean, belonging to a panel of diversity in order to obtain data that can be used in the growth of Brazilian soybean breeding programs